Recent Progress in Enantioselective Synthesis of γ-Lactams Bearing Chiral α-Quaternary Carbons - Sun, Yanan; Xu, Weiwei; Ye, Mengchun (Synlett, 2025)
The enantioselective construction of γ-lactams bearing chiral α-quaternary carbons represents a significant challenge in organic synthesis due to steric and stereoelectronic constraints. This Synpact highlights recent advancements in two complementary strategies: (1) ring decoration of preformed γ-lactams via asymmetric functionalization and (2) ring construction through transition metal–catalyzed carbonylative cyclization. Emphasis is placed on emerging methods utilizing inert C(O)–H/CN precursors, with an analysis of recent advancements, current limitations, and future directions.
Keywords: γ-Lactams; Chiral quaternary carbon; Transition metal catalysis; Organic catalysis; Carbonylative cyclization